Pengaruh Suku Bunga Terhadap Kinerja Perbankan Syariah di Provinsi Aceh - Bismi Khalidin Khalidin (Media Syari'ah, 2017)
It is widely known that interest rate is the core variable in a banking industry. Moreover, the performance of conventional banks are absolutely determined by the rate. However, the rate is prohibited to be utilized in an Islamic banking system. This paper aims at exploring the influence of interest rate towards the performance of Islamic banks in Aceh Province. In the other word, the paper is to know whether the rate influences Islamic banks or not. By Using two statistical softwares, E-Views 7 and SPSS-19, this research finds that the interest rate does not influence the performance of the Islamic banks.The performance of the banks under the research limites only deposits and financing of the banks. Either Granger Causality Test or Pearson Correlation indicates that there are no correlation between the variables in the model. However, the research does not have enough data, therefore the same research with more completed data is recommended.